2013
DOI: 10.1055/s-0032-1328198
|View full text |Cite
|
Sign up to set email alerts
|

Echinacea sanguinea and Echinacea pallida Extracts Stimulate Glucuronidation and Basolateral Transfer of Bauer Alkamides 8 and 10 and Ketone 24 and Inhibit P-glycoprotein Transporter in Caco-2 Cells

Abstract: The use of Echinacea as a medicinal herb is prominent in the United States, and many studies have assessed the effectiveness of Echinacea as an immunomodulator. We hypothesized that Bauer alkamides 8, 10 and 11 and ketone 24 were absorbed similarly either as pure compounds or from Echinacea sanguinea and Echinacea pallida ethanol extracts, and that these Echinacea extracts could inhibit P-glycoprotein transporter (P-gp) in Caco-2 human intestinal epithelial cells. Using HPLC analysis, the permeation rate of Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…We mention here specifically 2,4,6-octatrienoic acid ( 3b in Table 1 ) that may be used as tanning promoter and antioxidant in skin care products [13] . Moreover, a large class of natural polyunsaturated monocarboxylic acid amides [ 14 , 15 , 16 , 17 , 18 ] of the formula R-CH CH-CH CH-CO-NH-isobutyl, wherein R signifies a saturated or an unsaturated aliphatic group may now come into facile synthesis. They exhibit a wide range of biological properties and a corresponding range of possible utilities, notably as modulators or enhancers for the immune system [ 14 , 15 , 16 ] or as insecticides [ 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…We mention here specifically 2,4,6-octatrienoic acid ( 3b in Table 1 ) that may be used as tanning promoter and antioxidant in skin care products [13] . Moreover, a large class of natural polyunsaturated monocarboxylic acid amides [ 14 , 15 , 16 , 17 , 18 ] of the formula R-CH CH-CH CH-CO-NH-isobutyl, wherein R signifies a saturated or an unsaturated aliphatic group may now come into facile synthesis. They exhibit a wide range of biological properties and a corresponding range of possible utilities, notably as modulators or enhancers for the immune system [ 14 , 15 , 16 ] or as insecticides [ 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since then, however, studies have reported immunoactivity attributable to alkamides (Lalone 2009; Matthias 2008) and have suggested that influences on inflammatory pathways are complex, with both pro- and anti-inflammatory effects reported (Birt 2008; Qiang 2013; Yu 2013). Echinacea alkamides have been shown to be absorbed into the blood (Matthias 2005; Woelkart 2005b; Woelkart 2006; Woelkart 2008) and appear to exert a variety of effects through the endocannabinoid system (Chicca 2009; Woelkart 2005a; Woelkart 2007).…”
Section: Introductionmentioning
confidence: 99%